Tamadun Islam dan Tamadun Asia Tenggara (TITAS) learning portal for FCSIT students - Khairunnisa, Ibrahim (Universiti Malaysia Sarawak (UNIMAS), 2015)
This project is designed to for the students in the Faculty of Computer Science and Information Technology(FCSIT) UNIMAS as medium for them to learn TITAS course. The proposed system provides a self-learning pace for the students, where they will be given three choice of options which are whether to practice creating mind map, answering quiz questions and to search for terms meaning in TITAS course. By introducing this new system, learning TITAS can become more fun and the students' interest in TITAS can be increased. This system proposes features that a different from the features offered by UNIMAS MORPHEUS and OpenLearning for TITAS course. Therefore, it can be considered as a complement to these systems for the students to study TITAS course more effectively.